RNA-Binding Domain is Necessary for PprM Function in Response to the Extreme Environmental Stress in Deinococcus radiodurans - Li, Wei (Indian J Microbiol, 2017)
Deinococcus radiodurans was considered as one of the most radiation-resistant organisms on Earth because of its strong resistance to the damaging factors of both DNA and protein, including ionizing radiation, ultraviolet radiation, oxidants, and desiccation. PprM, as a bacterial cold shock protein homolog, was involved in the radiation resistance and oxidative stress response of D. radiodurans, but its potential mechanisms are poorly expounded. In this study, we found that PprM was highly conserved with the RNA-binding domain in Deinococcus genus through performing phylogenic analysis. Moreover, the paper presents the analysis on the tolerance of environmental stresses both in the wild-type and the pprM/pprM RBD mutant strains, demonstrating that pprM and RNA-binding domain disruptant strain were with higher sensitivity than the wild-type strain to cold stress, mitomycin C, UV radiation, and hydrogen peroxide. In the following step, the recombinant PprM was purified, with the finding that PprM was bound to the 5’-untranslated region of its own mRNA by gel mobility shift assay in vitro. With all these findings taken into consideration, it was suggested that PprM act as a cold shock protein and its RNA-binding domain may be involved in reaction to the extreme environmental stress in D. radiodurans. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12088-017-0684-y) contains supplementary material, which is available to authorized users.